Estudo dos possíveis efeitos da associação da Ginkgo biloba e ômega-3 na cognição de idosas saudáveis - Duarte, Débora do Espírito Santo Tobias [UNIFESP] (2010)
Several studies point to the beneficial effect of Ginkgo biloba and omega 3 on cognition in the elderly. The objective of this research was to verify whether the combined use of these substances enhances the cognitive functioning. The study was conceived as a double-blind, placebo-controlled, randomized trial. Altogether, 43 subjects between 60 and 70 years old, female, healthy, with more than 8 years of formal education, have ingested substances on a daily basis, for three months, according to the assigned treatment group: placebo+placebo (n=12), ginkgo+placebo (n=10), ômega3+placebo (n=11), ômega3+ginkgo (n=10), in the form of capsules that could contain 80 mg of ginkgo, 1 gram of fish oil (rich in omega 3) or placebo. Unlike other studies, we found no improvement in cognition of/in any of the four groups. The hypotheses suggested are: time of treatment or insufficient doses of substances.